Post-approval Surveillance on Safety and Clinical Utility of Garenoxacin Mesylate in Patients with Community Acquired Respiratory Tract Infections - Himanshu Garg; Pramod Harishchandra Katke; K Krishnaprasad (Journal of Clinical and Diagnostic Research, 2018)
Introduction: Respiratory Tract Infections (RTIs) have become increasingly difficult to treat owing to the increase in resistant Gram positive and Gram negative bacteria. Garenoxacin mesylate, a novel synthetic des-F(6)-quinolone has been approved in India in the year 2013 for treatment of bacterial RTIs. Aim: The aim of the present study was to perform a post marketing surveillance study on garenoxacin mesylate in the treatment of bacterial RTIs as a post approval requirement to assess the safety and clinical utility in Indian population. Materials and Methods: This study was a single-arm, phase IV, non-interventional, observational study to assess the safety profile of garenoxacin mesylate across eight established medical centers in India. Community acquired RTI patients were prescribed a single daily dose of garenoxacin mesylate 2×200 mg tablets administered orally for 5 to 14 days which included four follow up visits. A total of 461 patients were considered for analysis on safety as they had received at least a single dose. This subset was referred to as Safety Analysis Set (SAS). The primary endpoint of the study was to estimate the percentage incidence of adverse events experienced during the study with an intent to treatment basis. Clinical utility was assessed qualitatively based on the symptomatic improvement assessment done during each follow up. Results: The safety results were analysed for the intent to treat a population of 461 patients with community acquired RTIs. Baseline demographics showed 268 (58.1%) males and 193 (41.9%) female patient distribution with mean age of 33.7 years and comorbid history for 221 (45.8%) cases. Out of 461 patients, 53 (11.5%) patients developed 54 Treatment Emergent Adverse Events (TEAEs). The most common adverse drug reactions noted in 39 (74.1%) patients included abdominal discomfort (3, 0.6%), dizziness (10, 2.1%), headache (10, 2.1%) and decreased appetite (5, 1.1%). None of the patients reported serious adverse events including persistent symptoms that required drug discontinuation, hospitalisation or treatment with alternative drugs or antibiotics. Conclusion: Garenoxacin mesylate demonstrates excellent tolerability and safety profile and offers a therapeutic strategy in the management of bacterial or atypical RTIs.